Rumen-protected choline and vitamin E supplementation in periparturient dairy goats: effects on milk production and folate, vitamin B12 and vitamin E status - L. Pinotti (Animal, 2008)
We investigated the effects of rumen-protected choline (RPC) and vitamin E (VITE) administration on milk production and status of folate, vitamin B12 and vitamin E during the periparturient period of dairy goats. Forty-eight Saanen multiparous goats were selected for the 72-day experiment, being moved to a maternity pen 30 days before expected parturition and assigned to one of the four experimental groups: control (CTR), no choline or vitamin E supplementation; choline (RPC), supplemented with 4 g/day choline chloride in rumen-protected form; vitamin E (VITE), supplemented with 200 IU/day vitamin E in rumen-protected form; and choline and vitamin E (RPCE), supplemented with 4 g/day RPC chloride and 200 IU/day vitamin E. Supplements were administered individually before the morning feed to ensure complete consumption, starting 30 days before kidding and continuing for 35 days after. During the experiment, milk yield and 4% fat-corrected milk (FCM) yield were, respectively, 210 and 350 g/day higher in RPC-supplemented goats than in non-supplemented goats. Milk fat concentration and fat yield were also increased by RPC treatment. Milk yield and composition were unaffected by vitamin E supplementation. There were no significant interactions between RPC and VITE for any of the variables measured. Plasma metabolites did not differ between treatments before and after kidding except that plasma folate at parturition was higher in RPC-supplemented goats. Neither choline nor vitamin E affected vitamin B12 plasma concentrations, while a time effect was evident after the second week of lactation, when B12 levels in each treatment group started to increase. Vitamin E administration resulted in plasma α-tocopherol levels that were 2 to 2.5 times higher than in non-supplemented goats. Overall, these results suggest that greater choline availability can improve milk production and methyl group metabolism in transition dairy goats.